2016
DOI: 10.1186/s40814-016-0098-3
|View full text |Cite
|
Sign up to set email alerts
|

Can a mindfulness-informed intervention reduce aggressive behaviour in people with intellectual disabilities? Protocol for a feasibility study

Abstract: BackgroundApproximately 10–20 % of adults with intellectual disabilities engage in challenging behaviours such as aggression, destructiveness, and self-injury, which are often accompanied by feelings of anger. The inability to manage anger can reduce quality of life. For example, aggression is a strong predictor of out-of-area placements and is a risk variable for abuse. Recent research suggests that mindfulness-based therapies (specifically, Singh’s Soles of the Feet meditation) can help people with intellect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…This qualitative study was part of a larger feasibility study which recruited 19 people with ID who engaged with UMAA-LD SoF and retained 14 participants at the 6-month follow up. The protocol of the feasibility study is detailed in Griffith et al (2016). Broadly, recruitment was via clinician referral in NHS ID services in Wales, and UMAA-LD SoF was delivered within NHS services.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This qualitative study was part of a larger feasibility study which recruited 19 people with ID who engaged with UMAA-LD SoF and retained 14 participants at the 6-month follow up. The protocol of the feasibility study is detailed in Griffith et al (2016). Broadly, recruitment was via clinician referral in NHS ID services in Wales, and UMAA-LD SoF was delivered within NHS services.…”
Section: Methodsmentioning
confidence: 99%
“…MBPs have the practice of mindfulness as a central methodology, whereas mindfulnessinformed interventions draw upon the practice and philosophy of mindfulness, but also integrate other methodologies into the program. The intervention was delivered over six sessions, with sessions approximately 1 week apart, and is further described in Griffith et al (2016). In brief, core SoF meditations by Singh et al (2008) were used as a basis, during which participants were taught to recall situations that made them angry, then guided through the steps of the SoF meditation.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Griffith et al (2016) suggested that interventions integrating mindfulness may be useful for people with ID, as unlike multicomponent procedures, the core of mindfulness is centred on one aspect: the ability to shift the focus of one's attention, allowing an individual time to calm themselves and choose how to react to a triggering thought or event (Adkins et al 2010). There are many definitions of mindfulness; however, it is generally understood as intentionally focusing one's attention on the present moment experience, in a non-judgemental and accepting way (Kabat-Zinn 1990).…”
mentioning
confidence: 99%
“…A number of small-scale studies have demonstrated the success of SoF with people with ID who have aggressive behavior with reductions or elimination of aggressive behaviors at long-term follow-up (Adkins et al 2010;Singh et al 2007;Singh et al 2008a;Singh et al 2011b). Singh's SoF intervention (Singh et al 2003) has primarily been researched in the USA, involves extensive training, and includes little in terms of a taught psychoeducational component regarding emotional problems or about mindfulness (Griffith et al 2016). Additionally, SoF delivery in the USA demonstrated significant cost savings as a result of a reduction in staff absenteeism (Singh et al 2008a).…”
mentioning
confidence: 99%
“…The study also aimed to develop and carry out a preliminary test of the acceptability and accessibility of the Mindful Awareness for Adults with an Intellectual Disability Scale (MAIDS) with further analysis of reliability and validity if positively indicated. We also calculated the costs of the UK SoF intervention and evaluated the acceptability and validity of the health economic outcomes (Griffith et al 2016).…”
mentioning
confidence: 99%